Efficacy of Surface Treatments on the Bond Strength of Resin Cements to Two Brands of Zirconia Ceramic - Baldissara, Paolo; Querze, Marco; Monaco, Carlo; Scotti, Roberto; Fonseca, Renata Garcia [UNESP] (Quintessence Publishing Co Inc, 2013)
Purpose: To compare the shear bond strength (SBS) of two cements to two Y-TZP ceramics subjected to different surface treatments.Materials and Methods: Zirconia specimens were made from Lava (n = 36) and IPS e.max ZirCAD (n = 36), and their surfaces were treated as follows: no treatment (control), silica coating with 30-mu m silica-modified alumina (Al2O3) particles (CoJet Sand), or coating with liners Lava Ceram for Lava and Intensive ZirLiner for IPS e.max ZirCAD. Composite resin cylinders were bonded to zirconia with Panavia F or RelyX Unicem resin cements. All specimens were thermocycled (6000 cycles at 5 degrees C/55 degrees C) and subjected to SBS testing. Data were analyzed by post-hoc test Tamhane T2 and Scheffe tests (alpha = 0.05). Failure mode was analyzed by stereomicroscope and SEM.Results: With both zirconia brands, CoJet Sand showed significantly higher SBS values than control groups only when used with RelyX Unicem (p = 0.0001). Surface treatment with liners gave higher SBS than control groups with both ceramic brands and cements (p < 0.001). With both zirconia brands, the highest SBS values were obtained with the CoJet and RelyX Unicem combination (> 13.47 MPa). Panavia F cement showed significantly better results when coupled with liner surface treatment rather than with CoJet (p = 0.0001, SBS > 12.23 MPa). In untreated controls, Panavia F showed higher bond strength than RelyX Unicem; the difference was significant (p = 0.016) in IPS e.max ZirCAD. The nontreated specimens and those treated with CoJet Sand exhibited a high percentage of adhesive and mixed A (primarily adhesive) failures, while the specimens treated with liners presented an increase in mixed A and mixed C (primarily cohesive) failures as well as some cohesive failure in the bulk of Lava Ceram for both cements.Conclusion: CoJet Sand and liner application effectively improved the SBS between zirconia and luting cements. This study suggests that different interactions between surface treatments and luting cements yield different SBS: in clinical practice, these interactions should be considered when combining luting cements with surface treatments in order to obtain the maximum bond strength to zirconia restorations.
Keywords: zirconia; air abrasion; silica coating; resin cements; bonding; ceramic liner